Development of a Multidisciplinary Approach to Compute Sustainability Indices for Semiconductor Manufacturing Plant - a Singapore Perspective - Narayanaswamy Venkataraman , (2018)
Semiconductors are made of a solid crystalline material, usually silicone, formed into a simple diode or many integrated circuits. Semiconductor industries, which consumes large amounts of chemical and energy and large volumes of water, falls under the high hazard installation category in Singapore. Sustainability index computation and eventually benchmarking has not been studied for any privately listed companies in Singapore and in particular not studied for semiconductor manufacturing plants in Singapore. The objective of the study will be to determine the broad based parameters on sustainability indicators, determine the relationship between various parameters of sustainability, develop weightage factor for each parameters and develop a working model that will compute sustainability indices for semiconductor manufacturing environment in Singapore. Survey questionnaire was used and analysis of survey was done using known tools such as SPSS. Analytical hierarchy Process was used for computing weightage for the various parameters of sustainability. Based on the various models on sustainability, the proposed model involves four major constructs namely, management, employee wellbeing, resources and compliance. In the model chosen for this study, Sustainability index (SI) is a function of organization’s wellbeing, (W), Resources (R), Compliance (C), and possession of a management system (M). Being a versatile decision making tool, Analytical hierarchy process (AHP) model was used to determine the weightage for each functional element. A simplified formula was computed for this study, which is SI = (0.375*Wellbeing+ 0.25*Compliance+ 0.25*Resource+ 0.125*Management)/5. SI for the two companies were deduced from the survey and substituting these values in the equation for SI, SI for company A was computed as 80% and for company B it was computed as 85%. This meant SI for company B was better than that of company A and that company B is less riskier than company A A working model thus was formed for sustainability indexing for semiconductor manufacturing plants in Singapore, which can be extended to other manufacturing plants in Singapore and region. Further the study can be improved by incorporating other parameters such as economics. (Abstract by Author)